Enzymatic hydrolysis of Moringa oleifera Lam flour using bromelain and fig by-products as sources of protease - Bustamante, Lady Johana Arismendi [UNESP]; Maisa, Davanso [UNESP]; de Cerqueira e Silva, Mariana Barros; de Paula, Ariela Veloso [UNESP]; Teixeira, Estelamar Maria Borges; Bassan, Juliana Cristina [UNESP] (Elsevier, 2022)
Moringa oleifera Lamarck flour (MOF) has been recognized as a source of vegetable proteins; however, around 70.1±0.98% of protein can be called “insoluble protein”, for its resistance to gastrointestinal digestion. For protein to be absorbed in the human intestinal tract, it must be consumed in the form of a soluble protein. Proteases have shown to increase soluble proteins. The objective of this study was, hence, to investigate the increase in soluble proteins of MOF soluble and insoluble water fraction through the hydrolysis with proteases obtained from fig and pineapple by-products, ficin and bromelain, respectively. In conclusion, the protein of MOF had changes in their solubility by enzymatic effect. In particular, the hydrolysis of water insoluble Moringa oleifera Lam flour fraction (IMOF) with ficin contributed to a significant increase in soluble proteins, a result detectable through the different methods applied (colorimetric Bradford method, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and Reversed phase high-performance liquid chromatography (RP-HPLC)).
Keywords: By-product; Enzymatic hydrolysis; Fig latex; Moringa oleifera leaves; Pineapple crown; Protein